The relationship between quality of the working environment, workers' health and well-being Evidence from 28 OECD countries - Murtin, Fabrice (OECD Papers on Well-being and Inequalities, 2022)
This paper operationalises the OECD Guidelines for Measuring the Quality of the Working Environment (OECD, 2017) to describe job characteristics among European countries, the United States and Korea in 2010 and 2015. The analysis extends the range of aspects of quality of the working environment beyond those featuring in the Job Strain index presented by (Cazes, 2015), which is used to monitor implementation of the OECD Job Strategy, but at the cost of a more limited country coverage. While the two indices of job strain are largely consistent both across countries and over time, all of the job characteristics included in the "extended" index turns out to matter for workers' well-being. The framework uses the job demands-resources model ( (Demerouti, 2001) that stresses the importance of balancing the demands of the job and the resources that are available to workers to meet those demands.